HAEMOGLOBIN CONCENTRATION DIFFERENCES BETWEEN SINGLE AND MIXED SOIL- TRANSMITTED HELMINTH INFECTIONS IN SCHOOL- AGE CHILDREN - Nasution, Sri Wahyuni; Panggabean, Yoan Carolina; Pasaribu, Ayodhia Pitaloka (Pena Cendekia Insani, 2025)
Soil-transmitted helminths (STHs) remain among the most prevalent parasitic infections worldwide, particularly in developing countries. Persistent infections can lead to malnutrition, anemia, and impaired cognitive development. However, limited research has examined differences in hemoglobin concentration between children with single versus mixed STH infections. This study aims to compare the hemoglobin levels in school-age children at Al-Jam’iyatul Washliyah Orphanage, Medan, with single and mixed STH infections. A cross-sectional design was employed, involving elementary school children. Stool samples were analyzed using the Kato-Katz method to identify STH species and classify infection type, while hemoglobin levels were measured with a portable analyzer. Data were analyzed using independent t-tests, with statistical significance set at p < 0.05. A total of 150 children participated, with an overall STH infection prevalence of 18.8%; of these, 76.9% had single infections and 23.1% had mixed infections. Mean hemoglobin concentration was significantly lower in children with mixed infections compared to those with single infections (XX ± SD g/dL vs XX ± SD g/dL, p < 0.05). Mixed STH infections were associated with greater reductions in hemoglobin levels than single infections. Targeted deworming and nutritional interventions are essential to reduce anemia risk among vulnerable child populations.